2011
DOI: 10.1016/j.mee.2010.10.041
|View full text |Cite
|
Sign up to set email alerts
|

RF-MEMS load sensors with enhanced Q-factor and sensitivity in a suspended architecture

Abstract: In this paper, we present and demonstrate RF-MEMS load sensors designed and fabricated in a suspended architecture that increases their quality-factor (Q-factor), accompanied with an increased resonance frequency shift under load. The suspended architecture is obtained by removing silicon under the sensor. We compare two sensors that consist of 195 μm × 195 μm resonators, where all of the resonator features are of equal dimensions, but one’s substrate is partially removed (suspended architecture) and the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Prior work by our group has undertaken an extensive series of experimental and analytical analyses that included resonance response frequency (RRF) computational models, prototype fabrication, and ex vivo simulations which clearly demonstrated the feasibility of using MEMS technology to telemetrically report on the mechanical environment of the plate‐sensor construct by monitoring shifts in the sensor's RRF …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work by our group has undertaken an extensive series of experimental and analytical analyses that included resonance response frequency (RRF) computational models, prototype fabrication, and ex vivo simulations which clearly demonstrated the feasibility of using MEMS technology to telemetrically report on the mechanical environment of the plate‐sensor construct by monitoring shifts in the sensor's RRF …”
Section: Methodsmentioning
confidence: 99%
“…Prior work by our group has undertaken an extensive series of experimental and analytical analyses that included resonance response frequency (RRF) computational models, prototype fabrication, and ex vivo simulations which clearly demonstrated the feasibility of using MEMS technology to telemetrically report on the mechanical environment of the plate-sensor construct by monitoring shifts in the sensor's RRF. [10][11][12][13][14][15][16][17] There are two separate components to the bioMEMS system: (1) the bioMEMS sensor-implant construct (Fig. 1); and (2) the external excitation/receiving apparatus consisting of an antenna ( Fig.…”
Section: Biomems Fabricationmentioning
confidence: 99%
“…Ann Transl Med 2021 | https://dx.doi.org/10.21037/atm-21-1853 implantable microelectromechanical sensors (bioMEMS) capable of quantifying, via external antenna, temporal changes to the mechanical strain on implanted orthopaedic hardware (31,(41)(42)(43)(44)(45)(46)(47)(48)(49). In a previous study, temporally repeated bioMEMS measurements detected statistically significant differences in normal and aberrant bone healing in an ovine fracture model in as few as 21 days postfracture (31), and use of flexible bioMEMS enabled sensor application to most types of orthopaedic hardware (49).…”
Section: Introductionmentioning
confidence: 99%
“…Our group has performed a series of experimental and analytical investigations of increasing complexity upon MEMS‐based telemetric measurements of local fracture mechanics by observing shifts in the sensor's resonance response frequency (RRF) using computational models, prototype fabrication, ex vivo simulations, and in vivo animal models . The current system is composed of a multi‐sensor fsBioMEMS sensor‐implant construct and an external excitation/receiving apparatus consisting of a multi‐antenna array and a network analyzer (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…There is a current lack of non‐invasive diagnostic measures to determine callus strength, a metric which is crucial in diagnosing the state of bone healing and the patient's ability to bear weight . Previous studies have shown success in the use of sensors to telemetrically quantify construct mechanical environment . Use of a single wireless, biocompatible, microelectromechanical system (BioMEMS) sensor has previously utilized the bone‐implant load sharing principle to successfully detect statistically significant differences in normal and delayed healing in an ovine animal model as early as 21 days post‐fracture .…”
mentioning
confidence: 99%